Time bandits [videorecording (DVD)] - Gilliam, Terry; Palin, Michael; Palin, Michael; Cleese, John; Connery, Sean; Duvall, Shelley, 1949-2024; Helmond, Katherine; Holm, Ian, 1931-2020; Richardson, Ralph, Sir, 1902-1983; Vaughan, Peter, 1923-2016; Warner, David, 1941-2022; Rappaport, David, 1951-1990; et al. (Criterion collection, 2014)
A boy named Kevin escapes his gadget-obsessed parents to join a band of time-traveling dwarves. Armed with a map stolen from the Supreme Being, they plunder treasure from Napoleon and Agamemnon; but Evil is watching their every move. A giddy fairy tale, a revisionist history lesson, and a satire on technology gone awry.